Putting Age into Place: John Mighton’s Half Life and Joan Barfoot’s Exit Lines - Kriebernegg, Ulla (Age, Culture, Humanities: An Interdisciplinary Journal, 2015)
This paper addresses cultural constructions of old age in two contemporary Canadian care home narratives. While John Mighton’s play Half Life (2005) is set in a prison-like long-term care facility that is represented as a site of homogenization, oppression, and infantilization, Joan Barfoot’s novel Exit Lines (2008) plays in a hotel-like retirement lodge for wealthy customers that, despite its authoritarian manager, functions as a site of meaningful identity development and intragenerational relationships. What both texts have in common, however, is that they focus on residents’ individual resistance, subversion, and agency, thus opposing the ageist stereotype of decline and deconstructing prevailing norms and negative images of old age as merely physical decrepitude and disease. How is the space of the care home narrated in these two contemporary Canadian texts, and what role do aspects of space and place play for the narrative construction of old age? In this paper, I argue that the spatiality of aging is a category that needs to be incorporated into both an analysis of literary representations of the “fourth age” and an exploration of critical issues of space and place. The juxtaposition of two caregiving institutions in recent Canadian fction contributes to revealing how old age is imagined at the beginning of the twenty-frst century.